THE SECOND LIFE OF EVERYDAY OBJECTS IN BARRY FELDMAN’S WORK - Kertemelidou, Paraskevi; Warner, Randall (Design/Arts/Culture, 2022)
The following text makes special reference to the transfer of common industrial objects from the category of utility or even waste to autonomous works of art. The concept and image of the industrial object as garbage, by-product or as a thing without value, has occupied the artists of Cubism, Dada, Pop Art, Fluxus and Conceptual Art more recently (Cornell, Schwitters, Duchamp, Arman, Rauschenberg, Oldenburg, among many others). Barry Feldman, a New York artist and art historian, discovered through the permanent collection of MoMA avant-garde art and when he moved to Greece his New York experience remained alive for his work. Every industrial object finds its place in some of his three-dimensional compositions which he categorizes as boxes, portables, portholes and rockets. In wooden boxes, old or made by him, the worthless objects of our world are recycled and return to their autonomous existence.